Optimal Memory Allocation and Scheduling for DMA Data Transfers under the LET Paradigm - Pazzaglia, Paolo; Casini, Daniel; Biondi, Alessandro; Natale, Marco Di (2021 58th ACM/IEEE Design Automation Conference (DAC), 2021)
The Logical Execution Time (LET) paradigm is increasingly used to achieve predictable communications in modern multicore automotive applications. Direct Memory Access (DMA) engines can perform the data copies that are needed in a LET implementation on behalf of the cores with improved parallelism and reduced overheads. However, each DMA transfer operates on contiguous memory areas, and the performance is strongly dependent on the allocation in memory of the variables to be copied. This paper proposes a protocol to perform LET communications with a DMA and presents an optimal memory allocation scheme and scheduling using a mixed-integer linear programming formulation. Experimental results are reported to compare the performance of different communication approaches.